Materiale Textkulturen: Konzepte - Materialien - Praktiken - Meier, Thomas; Ott, Michael R.; Sauer, Rebecca (Materiale Textkulturen, 2015)
How does one define and explore the "material presence of the written in non-typographical cultures?" The interdisciplinary and collaborative essays in this handbook present theoretical principles, describe text-bearing materials and objects, and investigate the diverse practices related to text-bearing artifacts. The analysis is illustrated with examples drawn from a period of over 4,500 years.
Keywords: Aufsatzsammlung; Geschichte; Materialität; Text; Handlung; Schrift; Artefakt; Beschreibstoff